2016
DOI: 10.1016/bs.mcb.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Working with zebrafish at postembryonic stages

Abstract: As the processes of embryogenesis become increasingly well understood, there is growing interest in the development that occurs at later, postembryonic stages. Postembryonic development holds tremendous potential for discoveries of both fundamental and translational importance. Zebrafish, which are small, rapidly and externally developing, and which boast a wealth of genetic resources, are an outstanding model of vertebrate post-embryonic development. Nonetheless, there are specific challenges posed by working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 80 publications
2
34
0
Order By: Relevance
“…5F,H). In accord with McMenamin et al (2016), WIKs attained developmental stages at slightly smaller SL than either WT/WA or EKW strains (Table 1). However, the timing of AT appearance in WIKs was highly consistent with EKW (Table 2 and ).…”
Section: Resultsmentioning
confidence: 63%
“…5F,H). In accord with McMenamin et al (2016), WIKs attained developmental stages at slightly smaller SL than either WT/WA or EKW strains (Table 1). However, the timing of AT appearance in WIKs was highly consistent with EKW (Table 2 and ).…”
Section: Resultsmentioning
confidence: 63%
“…All the quantitative criteria measured were correlated with both age and standard length, and as is the case for other teleost fish species, including Zebrafish ( D. rerio ) and tilapia ( Oreochromis mossambicus ), standard length is a better proxy than absolute age to describe developmental progression . In other species of Pomacentridae, studies have highlighted the high correlation between quantitative traits and the length of larval A. frenatus and A. perideraion (with a regression coefficients between 0.95 and 0.99), which has also been observed in A. ocellaris in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Even if SL is a better proxy to follow the larval development of A. ocellaris, there is likely some variability in developmental progress even within a given SL category; this has been observed in Zebrafish . Indeed, Parichy et al observed that for a given size, larvae may not be at the same developmental stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, developmental progress is more closely related to standard length than to age (Parichy et al, 2009;McMenamin et al, 2016). In analyzing mutants that exhibit differences in body size (e.g., plod2 -/-mutants exhibited severely diminished body size compared to WT siblings), it is difficult to discriminate to what degree altered phenotypes are attributable to differences in developmental progress, versus specific effects on skeletal function.…”
Section: Allometric Models Aid In Discriminating Mutant Phenotypes Mamentioning
confidence: 99%